Narrative of Self Identity: Cultural Clash in Exit West and Home Fire - Sanjel, Govinda (The Batuk, 2025)
In the present globalized world, unprecedented movements of people across borders have become very common. The movements traverse the unstable terrain of displacement and belonging. Whether it is propelled by technological advancements, educational opportunities, employment opportunities, or by internal conflict, war, oppression, persecution, suppression, and political instability, the movements have become unstoppable. Such migration has scaled up complexity in negotiations as individuals from across the world that straddle multiple cultures creating intercultural interactions. And, these intercultural interactions challenge the traditional, static conception of identity making it more fluid and complex. The study bases its analysis on the content of the selected two texts applying Social Identity Theory (SIT) developed by Henri Tajeful and John Turner and Cultural Conflict Theory, developed by Lewis A. Coser. It investigates character development, narrative structure, and thematic elements in Mohsin Hamid's Exit West and Kamila Shamsie's Home Fire; the two novels published in the same year -2017 by Pakistani-American and Pakistani-British novelists respectively. Through comparative analysis, the study concludes highlighting the nuanced ways in which self-identity manifests fluidity in response to cultural clashes. It further reveals the complexities of the process of self-redefinition offering insights for the broader implications to individuals of the globalized world.